PEMANFAATAN PEKARANGAN DALAM MENINGKATKAN PENDAPATAN MASYARAKAT - Latuan, Emirensiana; Timung, Andri Permata; Botahala, Loth (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2021)
Undertaking farming in the yard has several functions, including meeting community needs, increasing income, also supporting food security, and beautifying the area around the house. The purpose of this community service is to provide knowledge and assistance to the Doelolong community about farming by utilizing community yards. The method used is counseling and mentoring, data collection techniques, and data analysis. The results of community service show that the average area of the family yard used is 128.86 mÂ². From this area, the net profit is Rp. 177,634, or 76% of the proceeds from the sale. Meanwhile, when compared with the average household income of farmers, there was an increase of 26.72%.Keywords: undertaking farming, yardland, community, village, income